Social Media Usage Patterns in Port Industry: Implications for Port Promotion and Public Relations - Aylin ÇALIŞKAN; Soner ESMER (Journal of Eta Maritime Science, 2018)
While social media has been penetrating the daily lives of individuals, the businesses have started to develop new strategical approaches for using social media tools, since they understand the importance of this new area. This study aims to take a step on the gap about social media marketing in the port industry. The focused sample is container ports located in Turkey, but to gain more meaningful insights, a comparison is also made with the ports of Los Angeles, Rotterdam, and Antwerp. The post set on Facebook, which covers the 8 months’ period, was analyzed through a social media analytics software, and the most attractive topics and engagement levels were determined. It was found that the most attractive posts of ports with high engagement levels do not include any statement, image, or video about port service, infrastructure and superstructure, investments, or success stories. At the end of the study, suggestions are developed by supporting with real cases for ports’ social media management.